ROOT CAUSE ANALYSIS OF INCONSISTENT BACTERIAL CULTURE MEDIA QUALITY USING THE FISHBONE (ISHIKAWA) DIAGRAM: A CASE STUDY - Yulianto Ade Prasetya; Putri Setyawati; Sri Indah Kusumawati; Muhajiriansyah; Budi Hartono (Universitas Kadiri, 2026)
Inconsistent bacterial culture media quality can compromise diagnostic accuracy and laboratory reliability in clinical microbiology. This study aimed to identify the root causes of bacterial culture media quality inconsistency using a Fishbone (Ishikawa) Diagram approach. A descriptive qualitative case study was conducted at the Microbiology and Biotechnology Laboratory, Faculty of Health Sciences, Universitas Anwar Medika, Indonesia, based on three laboratory quality complaints involving poor bacterial growth, contamination of prepared media, and inconsistent antimicrobial susceptibility test results. Data were collected through direct observation of media preparation processes, review of standard operating procedures, equipment calibration records, and structured discussions with laboratory personnel. Root cause analysis was performed using the 6M framework, including man, method, material, machine, measurement, and environment. The analysis revealed that method-related and measurement-related factors were the most dominant contributors, particularly non-standardized media preparation procedures, absence of routine growth promotion and sterility testing, and instability of sterilization and incubation equipment. Human-related and environmental factors acted as secondary contributors. These findings indicate that culture media quality inconsistency is primarily driven by systemic process weaknesses rather than isolated individual errors. Implementation of standardized procedures, strengthened quality control systems, and regular equipment monitoring is essential to improve laboratory performance and diagnostic reliability.